Leadership influence on project area team "turnover" – Rio De Janeiro-Brazil - Silva, Sérgio Henrique Pereira Rodrigues; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2021)
This article shows the leadership styles applied on a mining project team, where the previous stakeholders’ point of view was analyzed and compared with the literature. The information used in this paper was collected from the data available on Google Academic and PECEGE-ESALQ-USP, where scientific articles were found and used as a base line for this single case study performed with six previous stakeholders. The field data were collected using a questionnaire containing open-ended questions and semi structured interviews, which were further analyzed and compared with the literature. The aim of this study is to identify the different leadership styles currently in place in the project engineering field and, based on the results, suggest a more suitable leadership approach. The leadership styles addressed in this study are: authoritative, laissez-faire, democratic and situation. The literature suggests a lack of self-worth and an overall negative working environment. The main contribution of this study is to propose the situation, democratic and transformational styles as being the most efficient ones to be adopted by the project management team from a mining company located in Rio de Janeiro, Brazil.
Keywords: Leadership; leadership styles; leadership profiles